Environmental stratification by analysis of genotype x environment interaction in maize - Ribeiro, Juliana Zanetti; de Almeida, Marina Isabel Mateus (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to perform the stratification of maize cropping environments in Paraná, Minas Gerais, and Bahia States, Brazil, using different methods, and to determine association and divergence levels between the stratification methods. Four methods were evaluated: the Lin’s traditional one; the one of environmental dissimilarity; the genotype x environment (GxE) interaction decomposition in simple and complex parts; and the factor analysis. These methods were applied to 48 maize experimental hybrids, evaluated in 11 cropping environments in the three Brazilian states, divided into two sets of experiments. Besides the hybrids, six commercial cultivars, common to both sets, were used as controls. Genotype x environment interaction was predominantly complex. The decomposition of GxE interaction in simple and complex parts and the stratification by factor analysis were strongly associated to each other, and moderately associated to the other methods. Furthermore, these methods are more rigorous in the stratification process, weighting more efficiently the magnitude of the GxE interaction.